Mild Metal‐Free Intramolecular Oxidative Alkylation of a Csp3H Bond Adjacent to a Nitrogen Atom: A Versatile Approach to Ring‐Fused Tetrahydroquinolines. Issue 5 (27th February 2013) - Zhang, Gen; Wang, Shoulei; Ma, Yunxia; Kong, Weidong; Wang, Rui
Abstract A metal‐free intramolecular oxidative cross‐coupling reaction for the constructing Csp3Csp3 bonds mediated by 2, 3‐dichloro‐5, 6‐dicyanobenzoquinone (DDQ) under mild conditions was realized for the first time. This novel strategy provides a simple, efficient, and environmentally friendly access to diverse ring‐fused tetrahydroquinoline derivatives.